Bit Stream Oriented Enumeration Tree Pruning Algorithm - 邱卫东 金凌 杨小牛 杨红娃 (Shanghai jiao tong da xue xue bao, 2011)
Packet analysis is very important in our digital life. But what protocol analyzers can do is limited because they can only process data in determined format. This paper puts forward a solution to decode raw data in an unknown format. It is certain that data can be cut into packets because there are usually characteristic bit sequences in packet headers. The key to solve the problem is how to find out those characteristic sequences. We present an efficient way of bit sequence enumeration. Both Aho-Corasick （AC） algorithm and data mining method are used to reduce the cost of the process.